2016
DOI: 10.1007/s11356-016-7921-5
|View full text |Cite
|
Sign up to set email alerts
|

Annual variations and effects of temperature on Legionella spp. and other potential opportunistic pathogens in a bathroom

Abstract: Opportunistic pathogens (OPs) in drinking water, like Legionella spp., mycobacteria, Pseudomonas aeruginosa, and free-living amobae (FLA) are a risk to human health, due to their post-treatment growth in water systems. To assess and manage these risks, it is necessary to understand their variations and environmental conditions for the water routinely used. We sampled premise tap (N = 26, N = 26) and shower (N = 26) waters in a bathroom and compared water temperatures to levels of OPs via qPCR and identified Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…M. avium had a higher relative abundance in distal taps than in recirculating lines and a higher abundance from the experimental rig taps than control rig taps. Similarly, higher numbers in stagnated first draw than in flushed hot water were observed in a bathroom distal tap, with a trend of increasing numbers with temperature (20–49°C) ( Dumoulin et al, 1988 ; Lu et al, 2017 ). P. aeruginosa can grow well at 37–42°C ( LaBauve and Wargo, 2012 ), but less Pseudomonas were found in hot water systems characterized by higher numbers of L. pneumophila ( Borella et al, 2004 ), similar to what we observed in Figure 4B .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…M. avium had a higher relative abundance in distal taps than in recirculating lines and a higher abundance from the experimental rig taps than control rig taps. Similarly, higher numbers in stagnated first draw than in flushed hot water were observed in a bathroom distal tap, with a trend of increasing numbers with temperature (20–49°C) ( Dumoulin et al, 1988 ; Lu et al, 2017 ). P. aeruginosa can grow well at 37–42°C ( LaBauve and Wargo, 2012 ), but less Pseudomonas were found in hot water systems characterized by higher numbers of L. pneumophila ( Borella et al, 2004 ), similar to what we observed in Figure 4B .…”
Section: Discussionmentioning
confidence: 82%
“…P. aeruginosa can grow well at 37–42°C ( LaBauve and Wargo, 2012 ), but less Pseudomonas were found in hot water systems characterized by higher numbers of L. pneumophila ( Borella et al, 2004 ), similar to what we observed in Figure 4B . While these different OPs do share some common features ( Falkinham, 2015 ), their detections and abundances showed different trends with respect to examined factors ( Lu et al, 2017 ), making it difficult to effectively control all of them using a single uniform strategy. The fact that several positive correlations between L. pneumophila and known protozoan hosts were confirmed suggests that the metagenomic approach provides information consistent with known microbial ecological relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable levels of heat, 101, 129 mature biofilm accumulation, 130, 131 and presence of eukaryotic hosts 132, 133 are the most frequently observed factors responsible for proliferation. Source-specific conditions, such as low disinfectant residual 134 and stagnant water, 135 both frequently found within premise plumbing, have also been shown to be conducive to Legionella growth.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and heterogeneity of water systems make it challenging to link NTM growth and persistence to a few definable factors; more work is required to develop distribution system management strategies to mitigate the presence of NTM.In contrast to distribution system studies, research on NTM in building plumbing is plentiful, likely due to the number of NTM infections linked to public buildings. Large surface area to volume ratios, intermittent stagnation, low disinfectant residuals, and warm temperatures make building plumbing a favorable environment for bacterial attachment and growth[50][51][52][53]. NTM have been found in numerous plumbing appurtenances, including faucets and showerheads[12,22,54].…”
mentioning
confidence: 99%